Turkey : Third Review Under the Stand-By Arrangement-Staff Report; Staff Statement; and News Brief on the Executive Board Discussion. (IMF Staff Country Reports; Country Report ;, 2002)
This paper examines Turkey's Third Review Under the Stand-By Arrangement (SBA). The Turkish authorities' perseverance with their economic program started to yield major gains in the first part of 2002. Through April 2002, the program outperformed expectations. With strong policy implementation, economic and financial indicators outperformed financial market expectations and program projections. In light of continued strong program implementation, the positive economic results achieved so far, and the broad-based support in Turkey to stay the course with the program strategy, the IMF staff recommends the completion of the third review.